ŚAKUNI REIMAGINED: FOLK NARRATIVES AND THE DECONSTRUCTION OF VILLAINY IN THE MAHĀBHĀRATA - Srishti; Goswami, Akansha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The lasting allure of the Mahābhārata stems from its ability to evolve, enabling society to revisit and reinterpret its narrative over time. This reinvention also offers its so-called 'villains,' who are often relegated to the 'rogues' gallery, an opportunity for redemption. Śakuni, the cunning maternal uncle of the Kauravas, is one such character. While Vyāsa’s epic paints him as a negative figure, folk interpretations offer alternative perspectives. In Saralā Das's Oriyā Mahābhārata, Śakuni is depicted not as the chief architect of the war, but rather as a victim of the political machinations within the Kaurava court. Likewise, sympathetic portrayals of Śakuni can be found in the Kalbelia traditions of Rajasthan and in the folk renditions from Kerala. This research employs narrative technique to challenge the vilification of Śakuni. Using psychoanalytical criticism and deconstruction, it seeks to explore lesser-known narratives and reconsider Śakuni’s role, freeing him from filial blame and repositioning him in the epic's broader universe.